HASIL PENELITIAN TERBARU: BENTUK DAN KARAKTER SITUS SEMARUM - Hery Priswanto (BRIN, 2015)
Ancient brick structures were found in 1990 in Semarum site in the regency of Trenggalek. Intensive research have been carried out since 2012 to 2014. Systematic excavation was conducted to disclose the form and character of the site. The Data collection research through excavation activities with qualitative research methods. The result showed that Semarum site is an ancient water reservoir made of brick measuring 24 m x 24 m. Absolute chronology determination is still in the process, while the relative date is estimated between the XI - XIII centuries AD or between Kadiri to MajÂ¬apahit period.